2019
DOI: 10.21577/0103-5053.20190092
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diagnostics of Dengue by Reverse Transcription-Loop Mediated Isothermal Amplification (RT-LAMP) in Disposable Polyester-Toner Microdevices

Abstract: Dengue is one of the most prevalent infectious tropical diseases in the world, with high incidence in over 100 countries. Rapid and reliable diagnosis of dengue is of great importance for public health. To simplify molecular diagnostics, isothermal amplification techniques have recently emerged as an alternative to conventional methods of deoxyribonucleic acid (DNA) amplification. Here, we developed a one-step method for dengue virus detection from real sample based on RT-LAMP (reverse transcription-loop media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Utilizing RT-LAMP technology, this device is capable of identifying the DENV4 strain in authentic serum samples in a single, streamlined step. The device obtained a Limit of Detection (LOD) of 0.8 fg/μL within 2 min [ 57 ].…”
Section: Isothermal Amplification Techniques On Microfluidic Platformsmentioning
confidence: 99%
“…Utilizing RT-LAMP technology, this device is capable of identifying the DENV4 strain in authentic serum samples in a single, streamlined step. The device obtained a Limit of Detection (LOD) of 0.8 fg/μL within 2 min [ 57 ].…”
Section: Isothermal Amplification Techniques On Microfluidic Platformsmentioning
confidence: 99%
“…Mendes et al (80) reported a miniaturized disposable polyester-toner device for molecular diagnosis. This uses the reverse transcription loop-mediated isothermal amplification (RT-LAMP) technique with only one step to detect the DENV4 target in real serum samples.…”
Section: Viral Diseasesmentioning
confidence: 99%
“… Pathogen Time Sensitivity Detection Method References Zika 20 min 10 −5 PFU Colorimetric ( Calvert et al., 2017 ) Ebola 15–20 min 256 copies Real-time fluorometer ( Oloniniyi et al., 2017 ) HIV 60 min 10 4 RNA copies/mL RT Quencher probe ( Rudolph et al., 2015 ) Influenza 60 min 0.1 RNA copies Phenol-red pH indicator ( Ahnet al. et al., 2019 ) Hepatitis B 15 min 2.2fg/µl Fluorometer ( Quoc et al., 2018 ) Dengue 15 min 0.8 fg/µl Colorimetric (SYBR Green I) ( Mendes et al., 2019 ) HPV 60 min 10 copies Colorimetric (SYBR Green I) ( Mudhigeti et al., 2019 ) H1N1 <40 min 10 copies RNA Real-time turbidimeter, UV ( Kubo et al., 2010 ) Encephalitis 70 min 50 pg RNA Lateral flow dipstick ( Deng et al., 2015 ) MERS-CoV 60 min 4 RNA copies Colorimetric (EvaGreen) ( Lee et al., 2017 ) West Nile virus 17 min 0.1 PFU Real-time turbidimeter ( Parida et al., 2004 ) …”
Section: Reverse Transcription Lamp (Rt-lamp)mentioning
confidence: 99%
“…Similarly, dengue, causing seasonal attacks, is still prevalent in large parts of the world, and needs early diagnosis before the multiplication of the virus. Mendes et al. (2019) developed RT-LAMP which can produce results in 15 min with high sensitivity (in femtograms).…”
Section: Reverse Transcription Lamp (Rt-lamp)mentioning
confidence: 99%